Towards an understanding of teaching and learning in selected eight grade middle schools in Hunan Province, China - Jie, Zeng (Animo Repository, 2008)
With the economic, scientific and social development, people in China are paying more and more attention to the education of their children, and the enthusiasm of getting involved in education of all circles of the society is increasingly surging. This study was intended to provide a better understanding of teaching and learning in selected eight grade middle schools in Hunan province, China. The researcher aimed to understand students’ learning approach and teachers’ teaching approach, exploring whether teachers’ approaches of teaching, the role of teachers and other factors such as school culture, exam pressure, parents’ expectation and teachers’ expectations were correlated with students’ learning. Five conclusions were obtained from the results. First, most students acquired surface approach to learning while few adopted deep approach to learning. Second, all teachers adopt teacher-centered teaching approach in the selected eight grade classrooms. Third, teachers who described using a teacher- focused teaching approach were more likely to be teaching students who report using a surface approach to learning. Fourth, the role of teachers was associated with students’ learning. Fifth, other factors such as exam pressure, parents’ expectations, teachers’ expectations and school culture also affected students’ school achievement by either helping to bolster or suppress students’ learning. Based on the findings and conclusions of this study, recommendations were made to provide some insight for educators and principals in middle schools in China. Key Words: surface and deep learning approach, teacher-focused classroom, student- focused classroom